2017
DOI: 10.1037/prj0000212
|View full text |Cite
|
Sign up to set email alerts
|

Visual perceptual remediation for individuals with schizophrenia: Rationale, method, and three case studies.

Abstract: Objective Few studies have evaluated the effects of visual-remediation strategies in schizophrenia despite abundant evidence of visual-processing alterations in this condition. Here we report preliminary, case study-based evidence regarding the effects of visual remediation in this population. Methods We describe the implementation of a visual-perceptual training program called ULTIMEYES (UE) and initial results through three brief case studies of individuals with schizophrenia. UE targets broad-based visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 70 publications
(142 reference statements)
2
9
0
1
Order By: Relevance
“…As expected, the ROSz participants exhibited significant neurocognitive impairment relative to the HC group [t (50) = 6.20, p < 0.001, Cohen's d = 1.75]. The magnitude of impairment was similar to our previous findings with a different ROSz patient cohort (43).…”
Section: Sample Characteristicssupporting
confidence: 85%
“…As expected, the ROSz participants exhibited significant neurocognitive impairment relative to the HC group [t (50) = 6.20, p < 0.001, Cohen's d = 1.75]. The magnitude of impairment was similar to our previous findings with a different ROSz patient cohort (43).…”
Section: Sample Characteristicssupporting
confidence: 85%
“…This is also comparable to the 93% retention rate of CST in healthy young adults carried out by the second author (co-investigator and developer of Sightseeing) and colleagues. Our preliminary work with participants with schizophrenia show that CST is well tolerated, and even enjoyed, as described in our recent publication [141]. Across our pilot-study participants, CS improved 32%, with an increase in the peak contrast spatial frequency of 1 cycle/degree (pre-training peak spatial frequency of 3.14 ± 0.24 vs post-training of 4.15 ± 0.70, p = 0.14, d = 0.96).…”
Section: Approach Preliminary Datasupporting
confidence: 55%
“…visual integration (Keane, Paterno, Kastner, & Silverstein, 2016;Postmes et al, 2014;Silverstein et al, 2009;Silverstein et al, 2012;Silverstein et al, 2015), visual search (Ferguson & Cane, 2017;Waszczuk, Brown, Eley, & Lester, 2015;Platt, Murphy, & Lau, 2015;Chen, 2011;Dias, Bickel, Epstein, Sehatpour, & Javitt, 2013), spatial frequencies perception (Butler, Thompson, Seitz, Deveau, & Silverstein, 2017;Flevaris, Martínez, & Hilyard, 2014;Graham & Meng, 2011;Green et al, 2009;Kim, Shim, Song, Im, & Lee, 2015;Shoshina, Shelepin, Vershinina, & Novikova, 2015;Silverstein, Demmin, & Bednar, 2017), color perception (Kogata & Iidaka, 2018;Malone et al, 2013;Silver & Bilker, 2015) and movement perception (Jahshan, Wynn, Mathis, & Green, 2015;O´Bryan, Brenner, Hetrick, & O´Donnell, 2014;Golomb et al, 2009) as well as visual illusions (King, Hodgekins, Chouinard, Chouinard, & Sperandio, 2017). Weckowics and Witney (1960), for instance, studied the effect of visual size perception of the Muller-Lyer illusion in patients with Schizophrenia and found that schizophrenics perceived larger illusion effects than controls, but the group of non-schizophrenic psychiatric patients also showed larger magnitude effects than controls but, in turn, lower than schizophrenics.…”
Section: Palabras Clavementioning
confidence: 99%